2017
DOI: 10.1183/23120541.00037-2017
|View full text |Cite
|
Sign up to set email alerts
|

Arterial stiffness in symptomatic smokers with normal lung function

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with cardiovascular morbidity and mortality. Arterial stiffness and endothelial dysfunction index are validated surrogate cardiovascular markers and are increased in subjects with COPD.We tested whether increased arterial stiffness and endothelial dysfunction occur in symptomatic smokers with no evidence of bronchial obstruction. Clinical and lung functional assessments were conducted in smoker subjects with chronic respiratory symptoms and in COPD pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Due to the prevalence of early onset of comorbidities in COPD, an early treatment of the disease could be suggested to prevent the burden of comorbid conditions, even if further studies are still required to confirm the efficacy of this approach. For example, an increased risk of cardiovascular disorders has been recently documented in smoker subjects who are symptomatic but have not developed airway obstruction [232]. It has been suggested that the long-lasting exposure to smoke is the driving factor that initiates the inflammatory process both in the lungs and in the arteries, which in turn promotes the excess cardiovascular risk in chronic respiratory patients.…”
Section: State-of-the-art and Open Problems In Copd: Gaps And Issuesmentioning
confidence: 99%
“…Due to the prevalence of early onset of comorbidities in COPD, an early treatment of the disease could be suggested to prevent the burden of comorbid conditions, even if further studies are still required to confirm the efficacy of this approach. For example, an increased risk of cardiovascular disorders has been recently documented in smoker subjects who are symptomatic but have not developed airway obstruction [232]. It has been suggested that the long-lasting exposure to smoke is the driving factor that initiates the inflammatory process both in the lungs and in the arteries, which in turn promotes the excess cardiovascular risk in chronic respiratory patients.…”
Section: State-of-the-art and Open Problems In Copd: Gaps And Issuesmentioning
confidence: 99%